Efektivitas Perjanjian Pranikah sebagai Upaya Preventif terhadap Kekerasan dalam Rumah Tangga terhadap Perempuan: Studi Kasus di Kecamatan Kademangan - Dierel Moch Dierel Amp; Ahmad Syaifuddin Romli (Journal of Innovative and Creativity, 2025)
This study examines the effectiveness of prenuptial agreements as a preventive legal instrument against domestic violence (DV) toward women, with a case study in Kademangan District. Prenuptial agreements, as regulated in Article 29 of Law No. 1 of 1974 and reinforced by Constitutional Court Decision No. 69/PUU-XIII/2015, hold strong legal legitimacy and are not contradictory to Islamic legal principles. However, their implementation in society remains significantly limited. Using a qualitative empirical approach, data were collected through in-depth interviews, observation, and document analysis. Findings reveal that low legal literacy, entrenched patriarchal culture, and lack of institutional socialization are key barriers to the application of prenuptial agreements. In theory, such agreements offer the potential to redefine power relations within marriage and prevent DV from the outset. This study recommends reforming premarital counseling curricula, involving religious leaders, and developing a contextual, accessible model of prenuptial agreements. With adequate institutional support and legal education, prenuptial agreements can serve as a strategic tool for the protection of women and the development of just and equitable family structures..